Doubling of the gallbladder in children with intrauterine growth retardation: two clinical cases - A. F. Kiosov; S. A. Mikhailova (Лечащий Врач, 2024)
Background. Several variants of congenital gallbladder anomalies are distinguished: by position (median, suprahepatic, intrahepatic), shape (kinks, constrictions), number (doubling or tripling), presence of partitions in the gallbladder. In case of doubling, gallbladders can differ in shape and size. As a rule, a smaller gallbladder is considered to be an additive gallbladder. The accessory bladder may be hypoplastic or rudimentary. Gallbladder doubling can be in the form of either a simple (simplest) form or a true (complete) doubling. Doubling of the gallbladder is a very rare pathology.Results. The paper presents two clinical cases of gallbladder doubling detected in children during the neonatal period. Doubling of the gallbladder in infants was diagnosed using ultrasound examination on an expert-class device. In the first and second cases, doubling of the gallbladder was found in full-term boys in the early neonatal period. Newborn babies with a doubling of the gallbladder were born with intrauterine growth retardation of the hypotrophic and hypoplastic type. After birth, infants were diagnosed with neonatal jaundice of 3-4 degrees according to Kramer, hyperbilirubinemia due to the predominance of the indirect fraction of bilirubin. Data for hemolytic disease and intrauterine infection in children have not been obtained. The liver and spleen are not enlarged. The gallbladder was not palpated. There was no clinic for cholestasis in newborn children. Urine and stool were stained. One child with a doubling of the gallbladder was found to have a congenital heart defect, a defect in the interventricular septum. After phototherapy, jaundice in children was stopped by the 15th day of life. In children with gallbladder doubling, there were no indications for surgical treatment. Thus, no clinical and laboratory features of the neonatal period were found in children with gallbladder doubling. In children with intrauterine growth retardation, there is a high risk of developing pathological conditions in the neonatal period, anomalies and congenital malformations are possible.